2020
DOI: 10.1515/cclm-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the association between prostate-specific antigen and diabetes: a systematic review and meta-analysis

Abstract: ObjectivesSeveral studies have shown an inverse association between diabetes mellitus and prostate cancer (PCa). Some researchers suggest that this relationship is due to reduced PCa detection in diabetics due to lower prostate-specific antigen (PSA) levels compared to non-diabetics. Our objective is to analyze the impact of diabetes on PSA in asymptomatic men without known prostate pathology and without prior prostate intervention.MethodsWe searched Medline (via PubMed), Embase and Scopus. We included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…9 There is also a lower PCa detection rate among individuals with DM2, which could be due to the association between DM2 and increased body fat mass with reduced androgen levels, which could lead to lower PSA levels in serum because the testosterone level controls the production of PSA. 6,14,15 This inverse association between DM and PCa is apparently not related to the age of the DM patient or the time elapsed since its diagnosis. 2…”
Section: Pathophysiology and Relationship Between Prostate Cancer And...mentioning
confidence: 88%
“…9 There is also a lower PCa detection rate among individuals with DM2, which could be due to the association between DM2 and increased body fat mass with reduced androgen levels, which could lead to lower PSA levels in serum because the testosterone level controls the production of PSA. 6,14,15 This inverse association between DM and PCa is apparently not related to the age of the DM patient or the time elapsed since its diagnosis. 2…”
Section: Pathophysiology and Relationship Between Prostate Cancer And...mentioning
confidence: 88%
“…Fukui et al [ 20 ] found that serum PSA levels were 10-16% lower in diabetic men than in healthy Japanese men, excluding the age group of 40-49 years. Bernal-Soriano et al [ 21 ] also concluded in a meta-analysis that diabetic men showed lower PSA levels than non-diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Inci et al [205] reported decreased levels of PSA in patients with liver cirrhosis in relation to reduced prostate volume in these patients and also lower testosterone and protein levels. Patients with diabetes presented lower PSA levels than healthy subjects [206], while an inverse correlation was observed with body mass index, with lower PSA concentrations in obese patients [207]. Patients with heart disease or those undergoing cardiac surgery may present increased PSA levels [208].…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 95%